Factor Influencing Brand Loyalty In The Indonesian Food And Beverage Sector - Keni Keni; Meilia Japiana (Jurnal Manajemen, 2022)
The purpose of this research is to determine whether brand identification, brand satisfaction, and social media marketing can predict brand loyalty of fast-food restaurants in Indonesia directly or indirectly through brand love. A total of 272 respondents who are customers of fast-food restaurants in Indonesia were successfully collected by using online questionnaire, then PLS-SEM was used to examine the data. The results implied that social media marketing, brand satisfaction, and brand love can positively and significantly predict brand loyalty. Furthermore, brand identification and brand satisfaction were able to predict brand love positively and significantly, while brand identification and brand satisfaction were able to positively and significantly predict brand loyalty through brand love. The expected contribution of this research is as a reference for firms to improve their products and formulate appropriate marketing strategies to increase customer loyalty and the excellence of restaurant business in Indonesia.